Analysis of overburden movement and side abutment pressure distribution in deep stope with varying coal seam thickness - Yang, Yongjie; Meng, Lingren; Yuan, Lei (Frontiers in Earth Science, 2023)
To investigate the overburden movement and the side abutment pressure distribution concerning the variation in deep mines with varying coal seam thickness, this study focused on the No. 72 mining area of Tianchen Coal Mine and obtained the following results:This study investigates overburden movement and side abutment pressure distribution during fully mechanized mining in deep mines with varying coal seam thickness, focusing on the No. 72 mining area of Tianchen Coal Mine. Key findings include: Variations in coal seam thickness within a stope lead to increased immediate roof thickness. When the coal seam thickness is 8 meters, the maximum immediate roof thickness reaches 18 meters. The roof is composed of a "Combined short cantilever-Voussoir beam" structure. Displacement curves of overburden in coal seam thickness-varying stopes exhibit asymmetry, with the overburden closer to the coal seam being more asymmetric. After post-goaf stabilization, the peak side abutment pressure decreases with increasing coal seam thickness and shifts deeper into the coal wall. Concurrently, the ultimate equilibrium area width expands. With an increase in coal seam thickness from 4m to 8m, the peak side abutment pressures decreased from 44.98 MPa to 41.04 MPa. The peak position shifted from a distance of 9m from the coal wall to 14m, while the stressrelaxation area expanded from 3 meters to 5 meters.At coal seam thicknesses of 4, 6, and 8 meters, peak side abutment pressures are 44.98 MPa, 43.18 MPa, and 41.04 MPa, respectively. Peak positions are at distances of 9, 12, and 14 meters from the coal wall, with the stress-relaxation area measuring 3, 4, and 5 meters, respectively. This research provides essential insights for safe and efficient mining in similar conditions.